Sensitization of supra-threshold pain responses—Translational aspects and mechanisms - Jonas, Robin; Schmelz, Martin (Frontiers in Network Physiology, 2022)
A substantial translational gap in pain research has been reflected by a mismatch of relevant primary pain assessment endpoints in preclinical vs. clinical trials. Since activity-dependent mechanisms may be neglected during reflexive tests, this may add as a confounding factor during preclinical pain assessment. In this perspective, we consider the evidence for a need for supra-threshold pain assessment in the pain research literature. In addition to that, we focus on previous results that may demonstrate an example mechanism, where the detection of neuron-glial interactions on pain seems to be substantially depending on the assessment of pain intensity beyond threshold levels.